Drying Process Habanero Chili Using a Hybrid-Solar-Fluidized Bed Dryer in Yucatán, México: Feasibility Analysis - Elizabeth Cortés Rodríguez; Isaac Pilatowsky Figueroa; Claudia A. Ruiz Mercado (New Approaches in Engineering Research Vol. 2, 2021)
Solar energy was used to boost the drying process of Habanero chilli. The drying of habanero chilli is a significant seasonal commodity for Mexican producers; however, this process is costly and wasteful of energy. To determine the market trend and the optimal drying conditions for redesigning the Habanero chilli drying process using a hybrid solar-electric energy system, a feasibility study was developed. There will be two stages to the new drying process: (a) an open solar dryer was used; (b) an existing pilot fluidized bed dryer was adapted with a low temperature solar collector for air heating. Habanero chili was dehydrated from 90% to 5% moisture in 10.3 h, with good quality product, available for commercialization. With an energy savings of 0.52 kg of natural gas per kg of fresh Habanero chilli, a 50% reduction in average drying time was achieved, as well as a % reduction in energy consumption in the fluidized bed dryer.In order to expand the market for Habanero chilli, an innovative sustainable efficient drying process was created, which will save % on energy when compared to conventional equipment.